1962
DOI: 10.1002/1097-4679(196210)18:4<396::aid-jclp2270180403>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of chronic schizophrenic patients and college students to facial expressions and geometric forms

Abstract: PROBLEMThe major purpose of this investigation was to determine whether chronic schizophrenic patients are deviant with respect to (a) ability to derive bipolar conceptual dimensions in terms of which sets of concrete materials (such as geometric forms or photographs of facial expressions) may be meaningfully arranged in rank order; (b) ability to rank these sets of materials in terms of a dimension of meaning after the bipolar concepts have been made explicit and anchor points have been provided; (c) their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The inconsistency is shown in the number of studies where, at least in part, schizophrenic performance has been normal. Thus, when supplied with category labels (Levy, Orr & Rosenzweig, 1960;Shannon, 1970;Spiegel, Gerard, Grayson & Gengerelli, 1962), schizophrenics perform as well as normal subjects. Other experiments (Pilowsky & Bassett, 1980;Ferdowsi, 1983;Walker, 1981) have found that schizophrenics perform at the same levels as neurotic o r depressed subjects.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The inconsistency is shown in the number of studies where, at least in part, schizophrenic performance has been normal. Thus, when supplied with category labels (Levy, Orr & Rosenzweig, 1960;Shannon, 1970;Spiegel, Gerard, Grayson & Gengerelli, 1962), schizophrenics perform as well as normal subjects. Other experiments (Pilowsky & Bassett, 1980;Ferdowsi, 1983;Walker, 1981) have found that schizophrenics perform at the same levels as neurotic o r depressed subjects.…”
mentioning
confidence: 91%
“…Many of the inconsistencies can be attributed to methodological differences. Firstly, none of the early studies quote diagnostic criteria for their schizophrenic subjects (Levy et aI., 1960;Shannon, 1970;Spiegel et al, 1962). In this study, RDC (Spitzer & Endicott, 1975) was used.…”
mentioning
confidence: 99%
“…(1989) found that, when compared with controls, acute schizophrenic patients were impaired on both types of tasks. An early study by Spiegel, Gerard, Grayson & Gengerelli (1962), which included a non-facial task, found that, when bipolar concepts and anchor points were provided, there were no differences in the performance of schizophrenic patients and normal controls on a task which involved ranking photographs of emotion expression and on non-facial tasks, one of which involved ranking circles from small to large.…”
mentioning
confidence: 99%
“…To date, studies with schizophrenics have given less consideration to auditory cues and concentrated on the recognition of facial expressions of emotion. Aside from one early negative report (Spiegel et a!, 1962) more recent studies have noted a deficit in facial affect recognition in at least some groups of schizophrenics (Shannon, 1970;Dougherty eta!, 1974;Muzekari and Bates, 1977;Kurucz Ct a!, 1979;Walker et a!, 1980;Walker, 1981;Cutting, 1981). However, there are several problems with these studies.…”
mentioning
confidence: 99%